OPTIMIZATION OF THE RETANNING PROCESS OF CHROME SEMIFINISHED LEATHER USING ALKYLCARBOXYETHANOLAMINE - ДАНИЛКОВИЧ, Анатолій; ОХМАТ, Олена (Technologies and Engineering, 2025)
Purpose. Optimization of the retanning process of chrome-tanned leather semifinished product with chromium compounds using alkylcarboxyethanolamine monoethanolamine and natural naphthenic acids (ACEA NNA) through mathematical modeling. Methodology. A mathematical description of the retanning process of the chrome-tanned semifinished product with basic chromium sulfate was obtained based on the implementation of a central composite rotatable second-order design. The retanning process was optimized by the scanning method using the mathematical description and Harrington’s desirability function. For this purpose, partial desirability functions were determined based on predefined worst and best compromise values of the output variables. A compromise region bounded by isolines within the established intervals ( ) for the i output variables (i = 1, 2) was constructed. The compromise region, with isolines of the desirability function plotted from zero to one, represents the optimal zone. Findings. The process of retanning chrome-tanned semifinished leather using basic chromium sulfate together with alkylcarboxyethanolamine monoethanolamine and natural naphthenic acids was studied. Optimization of the process was performed using the obtained mathematical model and Harrington’s desirability function. Significant factors affecting the quality indicators of the semifinished product were identified. As a result of the calculations using computer programs, optimal retanning parameters for chrome semifinished leather were determined to achieve the desired quality indicators. In this case, the consumption of basic chromium sulfate with a basicity of 33.5% was 1.14%, while the consumption of ACEA NNA was 0.62% of the semifinished product mass. The resulting leather semifinished product was characterized by a hydrothermal stability temperature of 117 °C and a residual Cr₂O₃ concentration in the spent solution of 8.32%. Originality. The technology of retanning chrome-tanned semifinished leather with basic chromium sulfate and ACEA NNA, due to the established optimal consumption rates, ensures the production of a semifinished product with enhanced hydrothermal stability. Practical value. The developed optimal retanning technology for chrome-tanned semifinished leather provides a semifinished product with improved hydrothermal stability and allows for the further efficient formation of elastic leather. The obtained research results can be applied in the development of new technologies for producing leather of a wide assortment.